Preparation and characterization of Pickering foams by mechanical frothing and emulsion templating - Fatma Nur Parın; Hatice Dinç; Uğur Parın; Elife Kıldalı; Gökçe Taner (eXPRESS Polymer Letters)
In this study, Pickering foamed emulsions have been prepared using β-cyclodextrin (β-CD), and d-limonene as a surfactant and an oil phase, respectively. The incorporation of β-CD/d-limonene inclusion complexes (ICs) in specific proportions (1:1, 1:3, and 1:5) to water phase, which is a polymer matrix composed of a mixture of polyvinyl alcohol (PVA) and psyllium husk (PSH) by mechanical frothing at high speed, and air bubbles have been formed in oil in water (o/w) emulsions. Ecofriendly bio-based foams have been developed in this method. Scanning Electron Microscope (SEM) analysis showed PVA/PSH Pickering foams usually open porous morphologies and the addition of d-limonene increases the amount of porosity from 43 to 49%. Although the resulting foams indicated similar thermal degradation profile, the presence of d-limonene in foams increased thermal stability. The surfaces of foams have a hydrophilic property with contact angles values lower than 80°. The tensile strength of foams decreased from 170 to 100 kPa due to the increased porosity. All foams indicated antibacterial activity to Staphylococcus aureus (S. aureus) with 9–12 mm zone inhibition. The incorporation of d-limonene into foams surprisingly decreased the cell viability. In brief, our findings show that the Pickering foams can be beneficial for wound healing applications.